2013
DOI: 10.1371/journal.pone.0063374
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Regulators during Atherogenesis: Expression of LXR, PPAR, and SREBP mRNA in the Human Aorta

Abstract: Transcription factors LXRs, PPARs, and SREBPs have been implicated in a multitude of physiological and pathological processes including atherogenesis. However, little is known about the regulation of these transcription factors at different stages of atherosclerosis progression. Quantitative real-time polymerase chain reaction (qRT-PCR) was used to compare the contents of mRNAs in pairs intact-injured aorta fragments taken from the same donors. Only minor changes in LXRα, LXRβ, PPARα, PPARγ, SREBP1, and SREBP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 24 publications
4
5
0
Order By: Relevance
“…Meanwhile, PPARs can also repress gene expression by antagonizing the activities of NF-κB and activator proteins [ 46 ]. Our results also demonstrated that PPAR gene expression and protein levels were both up-regulated in AS lesions of the abdominal aorta, which is consistent with the results of previous clinical studies by Shchelkunova et al [ 52 ]. Additionally, NF-κB protein and levels of its downstream inflammatory factors, such as IL-1β, TNF-α, ICAM-1, VCAM-1, MCP-1, MMP-9, and CRP were also increased in HFC-fed minipigs (Figure 8 ).…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, PPARs can also repress gene expression by antagonizing the activities of NF-κB and activator proteins [ 46 ]. Our results also demonstrated that PPAR gene expression and protein levels were both up-regulated in AS lesions of the abdominal aorta, which is consistent with the results of previous clinical studies by Shchelkunova et al [ 52 ]. Additionally, NF-κB protein and levels of its downstream inflammatory factors, such as IL-1β, TNF-α, ICAM-1, VCAM-1, MCP-1, MMP-9, and CRP were also increased in HFC-fed minipigs (Figure 8 ).…”
Section: Discussionsupporting
confidence: 93%
“…In BMDMs, DGAT2 mRNA levels were significantly decreased, while SREBP1 levels were significantly upregulated. A previous study investigating the effects of cholesterol loading on expression of lipid metabolism genes in human monocyte derived macrophages, also detected decreased SREBP2 expression upon lipid loading 28 , thus mimicking the results obtained in PEMs in our study. This study also analysed mRNA expression of selected lipid metabolism genes in vivo (in human atherosclerotic lesions vs normal artery) and concluded, amongst others, that there was only partial similarity between changes in expression levels of lipid metabolism genes during plaque progression in vivo and lipid loading in vitro 28 .…”
Section: Discussionsupporting
confidence: 90%
“…A previous study investigating the effects of cholesterol loading on expression of lipid metabolism genes in human monocyte derived macrophages, also detected decreased SREBP2 expression upon lipid loading 28 , thus mimicking the results obtained in PEMs in our study. This study also analysed mRNA expression of selected lipid metabolism genes in vivo (in human atherosclerotic lesions vs normal artery) and concluded, amongst others, that there was only partial similarity between changes in expression levels of lipid metabolism genes during plaque progression in vivo and lipid loading in vitro 28 . Although the 2 studies are difficult to compare directly, since there are differences in both the study setup, and the genes analysed, the fact that both studies only detect partial similarity of findings in vivo and in vitro highlights the difficulty in comparing, and trying to decipher, in vivo pathological pathways using in vitro model systems.…”
Section: Discussionsupporting
confidence: 90%
“…Results showed that SREBF2 mRNA was found comparable to non-diseased tissue in initial lesions. Otherwise SREBF2 transcript was found to be progressively up-regulated in fatty streaks and fibrous lipid plaques, supporting an active role of this biomolecule during the atherosclerosis progression [46]. The present study shows an association between the circulating expression levels of SREBF2 mRNA in PBMNCs and the presence of obstructive CHD.…”
Section: Discussionsupporting
confidence: 74%